Formulation and evaluation of transdermal drug delivery system of verapamil hydrochloride - Marapur, S C; Wali, D S; Hunasagi, B S; Chetankumar, M; Patil, R G (Journal of Drug Delivery and Therapeutics, 2018)
The aim of this research was to develop and evaluate a matrix type of transdermal drug delivery system containing Verapamil Hydrochloride. The series of formulations containing Verapamil Hydrochloride were formulated by using different polymers like HPMC (hydrophilic), CAP (hydrophobic) and EC (hydrophobic) in different ratios by solvent evaporation technique. Propylene glycol and Dibutyl phthalate were used as plasticizers. The 20% and 40% of DMSO is used as the penetration enhancer. Formulated transdermal patches were physically evaluated for thickness, weight variation, drug content, flatness, tensile strength, folding endurance, and water vapour transmission rate. The in-vitro drug release study was carried out by using Franz diffusion cell. The data obtained from release study shows increased percentage of drug permeated in 20% of DMSO containing formulation than 40% of DMSO containing formulation. Drug permeation is enhanced in the formulation containing high concentration of HPMC (VH1). The VH2 and VH6 helped in maintaining the rate of release at a constant level (20% DMSO). But in case of 40% DMSO is used as the concentration of CAP increases the rate of permeation increases. Skin irritation study does not show any irritation on the skin of rabbit. There is no possible interaction between drug and polymers in FITR as well as DSC. XRD of selected formulation shows that drug present in the formulation is in crystalline form. Keywords: Verapamil HCl, HPMC, EC, CAP, DMSO, TDDS, Solvent evaporation